Characterisation of mucosal tissue in the foreskin after voluntary medical male circumcision - Harryparsad, Rushil (Division of Immunology, 2016)
Background: Medical Male Circumcision (MMC) reduces the risk of HIV-1 acquisition by up to 60% as shown in a number of randomized controlled trials in Uganda, Kenya and South Africa. MMC has also been shown to reduce the prevalence of other sexually transmitted infections (STIs) like Herpes Simplex Virus (HSV) -2 and Human Papillomavirus (HPV) by 25% and 35% respectively. Asymptomatic STIs may elevate the risk of HIV-1 acquisition by recruiting HIV-1 target cells to the foreskin. The higher permeability of the inner foreskin may play a role in HIV-1 acquisition as well as the number of target cells present in the foreskin. The more inflamed inner foreskin may be increasing the risk of a productive HIV-1 infection. The aims of this dissertation was to a) examine the levels of keratinisation in the inner and outer foreskins after MMC; b) investigate the number of Langerhans, Ki67+ and CD4+ T cells in the inner and outer foreskin and c) identify the impact of asymptomatic STIs on the numbers and proliferative capacity of foreskin-resident Langerhans and CD4+ T cells.